BM-MSC Transplantation Alleviates Intracerebral Hemorrhage-Induced Brain Injury, Promotes Astrocytes Vimentin Expression, and Enhances Astrocytes Antioxidation via the Cx43/Nrf2/HO-1 Axis - Chen, Xiao; Liang, Huaibin; Xi, Zhiyu; Yang, Yong; Shan, Huimin; Wang, Baofeng; Zhong, Zhihong; Xu, Canxin; Yang, Guo-Yuan; Sun, Qingfang; Sun, Yuhao; Bian, Liuguan (Frontiers in Cell and Developmental Biology, 2020)
Intracerebral hemorrhage (ICH) is a particularly severe form of stroke, and reactive astrogliosis is a common response following injury to the central nervous system (CNS). Mesenchymal stem cells (MSCs) are reported to promote neurogenesis and alleviate the late side effects in injured brain regions. Gap junctions (Gjs) are abundant in the brain, where the richest connexin (Cx) is Cx43, most prominently expressed in astrocytes. Nuclear factor erythroid 2-related factor 2 (Nrf2) is an essential transcription factor regulating antioxidant reactions. Here, we aimed to explore whether bone marrow MSCs (BM-MSCs) could alleviate brain injury and protect astrocytes from apoptosis, by regulating Cx43 and Nrf2. We validated the effect of BM-MSC transplantation in an ICH model in vivo and in vitro and detected changes using immunofluorescence, as well as protein and mRNA expression of glial fibrillary acidic protein (GFAP), vimentin (VIM), Cx43, Nrf2, and heme oxygenase-1 (HO-1). Our results showed that BM-MSC transplantation attenuated brain injury after ICH and upregulated VIM expression in vivo and in vitro. Additionally, Cx43 upregulation and Nrf2 nuclear translocation were observed in astrocytes cocultured with BM-MSC. Knockdown of Cx43 by siRNA restrained Nrf2 nuclear translocation. Cx43 and Nrf2 had a connection as determined by immunofluorescence and coimmunoprecipitation. We demonstrated that astrocytes undergo astroglial-mesenchymal phenotype switching and have anti-apoptotic abilities after BM-MSC transplantation, where Cx43 upregulation triggers Nrf2 nuclear translocation and promotes its phase II enzyme expression. The Cx43/Nrf2 interaction of astrocytes after BM-MSC transplantation may provide an important therapeutic target in the management of ICH.